On the product of the self-adjoint operators - Wulf Rehder (International Journal of Mathematics and Mathematical Sciences)
A proof is given for the fact that the product of two self-adjoint operators, one of which is also positive, is again self-adjoint if and only if the product is normal. This theorem applies, in particular, if one operator is an orthogonal projection. In general, the positivity requirement cannot be dropped.